Transmathematica 2017: Transmathematics and The Philosophy of Numbers - Anderson, James A.D.W. (Transmathematica, 2019)
We present the call for papers and abstracts of the first Transmathematica conference, which was held in 2017 as Session 83, Transmathematics and the Philosophy of Numbers, of the 25th International Congress of History of Science and Technology (ICHST), Rio de Janeiro, Brazil, 23-29 July. In the absence of the present paper, the abstracts would otherwise have been lost from the public record.